Allelic variation and differential expression at the 27-kilodalton zein locus in maize. - Das, O P (1987)
Allelic variation between inbred lines at the 27-kilodalton zein gene locus in maize has been used to study gene expression in developing endosperm. The inbred lines W22 and W23 contain two genes for this protein within two tandem repeats; the individual genes are virtually identical, with 99.9% homology in the 5'-flanking regions. Using gene-specific oligonucleotide probes, we have shown that transcripts of the downstream gene are found at a 2.5-fold-higher level than those of the upstream gene. Another inbred line, BSSS53, has one copy of the gene which is a recombinant of the duplicated genes at the 3'-flanking region. This line has been used in reciprocal crosses to demonstrate dosage effects for the overexpression of the downstream gene and to show that the overexpression of mRNA is reflected in a corresponding increase in the protein level. The accumulation of the protein through development does not, however, always correspond to the difference in mRNA levels.